The Influence of KAP Reputation, Opinion Shopping, and Debt Default on Receipt Of Going Concern Audit Opinion - Indah Fitriani, SE., M.Si., Ak.,CA; Martina Putri Pestaria (Jurnal Riset Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of KAP reputation, opinion shopping, and debt default on the acceptance of going concern audit opinion. The population is energy  companies listed on the Indonesia Stock Exchange during  2019-2021 period. Purposive sampling method was used in this study with a total sample of 41 companies or 141 data. Data analysis using binary logistic regression analysis method. The results of this study indicate that:(1) KAP reputation affects the acceptance of going concern audit opinions,(2) Opinion shopping affects the acceptance of going concern audit opinions, (3) Debt default does not affect the acceptance of going concern audit opinions, (4) Reputation KAP, opinion shopping, and debt default  simultaneously affect the acceptance of going concern audit opinion.